Molecular and clinical characteristics of monogenic diabetes mellitus in southern Chinese children with onset before 3 years of age. Issue 1 (13th August 2020) - Lin, Yunting; Sheng, Huiying; Ting, Tzer Hwu; Xu, Aijing; Yin, Xi; Cheng, Jing; Mei, Huifen; Shao, Yongxian; Zeng, Chunhua; Zhang, Wen; Rao, Min; Liu, Li; et al.
Abstract : Introduction: A specific molecular diagnosis of monogenic diabetes mellitus (MDM) will help to predict the clinical course and guide management. This study aims to identify the causative genes implicated in Chinese patients with MDM with onset before 3 years of age. Research design and methods: 71 children with diabetes mellitus (43 diagnosed before 6 months of age, and 28 diagnosed between 6 months and 3 years of age who were negative for diabetes-associated autoantibodies) underwent genetic testing with a combination strategy of Sanger sequencing, chromosome microarray analysis and whole exome sequencing. They were categorized into four groups according to the age of onset of diabetes (at or less than 6 months, 6 to 12 months, 1 to 2 years, 2 to 3 years) to investigate the correlation between genotype and phenotype. Results: Genetic abnormalities were identified in 39 of 71 patients (54.93%), namely KCNJ11 (22), ABCC8 (3), GCK (3), INS (3), BSCL2 (1) and chromosome abnormalities (7). The majority (81.40%, 35/43) of neonatal diabetes diagnosed less than 6 months of age and 33.33% (3/9) of infantile cases diagnosed between 6 and 12 months of age had a genetic cause identified. Only 11.11% (1/9) of cases diagnosed between 2 and 3 years of age were found to have a genetic cause, and none of the 10 patients diagnosed between 1 and 2 years had a positive result in the genetic analysis. Vast majority or 90.48% (19/21) of patients with KCNJ11 (19) or ABCC8 (2) variants had successful switch trial from insulin to oral sulfonylurea. Conclusions: This study suggests that genetic testing should be given priority in diabetes cases diagnosed before 6 months of age, as well as those diagnosed between 6 and 12 months of age who were negative for diabetes-associated autoantibodies. This study also indicates significant impact on therapy with genetic cause confirmation.